REORIENTATION OF MUNAKAHAT FIQH LEARNING FROM A NORMATIVE-LEGALISTIC APPROACH TO MAQASHID SYARIAH-BASED REASONING AT AL ANSOR ISLAMIC BOARDING SCHOOL, PADANGSIDIMPUAN - Nur Sa’adah Harahap; Purnama Hidayah Harahap (PT. Jurnal Center Indonesia Publisher, 2026)
The teaching of fiqh munakahat in Islamic boarding schools is generally still dominated by a normative-legalistic approach, which emphasizes the determination of legal status, such as halal–haram or valid–invalid, based on texts and the authority of classical books. This approach is important in preserving the scholarly tradition of fiqh, but in practice it often does not encourage students to understand the legal objectives and social implications of fiqh provisions. This study aims to analyze how the maqāṣid syariah reasoning approach can be applied in the teaching of fiqh munakahat and how this approach influences the students' way of thinking. This study uses a qualitative approach with a case study design conducted at the Al-Ansor Islamic Boarding School in Padangsidimpuan. Data were collected through observation of the learning process in the classroom, discussions with students, and reflections from teachers during the field study. The results of the study show a shift in the students' way of thinking from a textual understanding of the law to a more reflective understanding, taking into account the social context and objectives of sharia. This research contributes by offering a more contextual, reflective, and relevant model of fiqh munakahat learning for the challenges of contemporary Muslim family life.